Incorporación de los avances en la aplicación de la política restitución de tierras a los planes de desarrollo con enfoque territorial. Caso de estudio: Municipio de Agustín Codazzi (2019)
The work, in effect, deals with one of the most sensitive phenomena of the national policy of the last fifty years, synthesized and raised in the research problem, which is to what extent the PDET that includes the Municipality of Agustín Codazzi, incorporates the Advances achieved in the implementation of the land restitution policy in that municipality regarding decent housing, support services, collective equipment and infrastructure for production; to ensure that the restoration not only seeks to return the land with its respective title, but also improve its socioeconomic conditions for a more dignified life and comprehensive reparation